Efektivitas Metode Learning Contratc Terhadap Motivasi Belajar Pratikum Instalasi Listrik Pada Mahasiswa Teknik Elektro Universitas Negeri Padang - Mai Yandra Fadillah; Hambali Hambali (Student Research Journal, 2023)
This research was motivated by the value of the Electrical Installation practicum for Electrical Engineering Students at Padang State University, there were low student grades, there were students who did not do the assignments given by the lecturer which made student grades low, and students who did not read enough material before taking part in the learning activities that were to be carried out. This research aims to determine the effectiveness of implementing the Learning Contratc method on learning motivation for Electrical Installation Practicum in Electrical Engineering Students at Padang State University. This research is a quantitative approach. The population in this study were all students of the 2022 class of Electrical Engineering at Padang State University using a random sampling technique. The analysis of this research is correlation. The results of this research show that the learning contract method has an influence on the motivation to learn electrical installation practicals in Electrical Engineering students at Padang State University.